Electronic structure of polyacetylene with bonded oxygen - Lavarda, Francisco Carlos [UNESP]; Galvão, Douglas S.; Laks, Bernardo (Elsevier, 1992)
In this work we have studied the electronic structure of finite polyacetylene chains with structural oxygen-bonding models following data from 13C-NMR experiments. We have used a combination of Austin Method One and Hydrogenic Atoms in Molecules version 3 methods to perform geometric and spectroscopic calculations. Our results show that the electronically-active states are generally unaffected by the incorporation of oxygen. © 1992.
Keywords: Electronic properties; Mathematical models; Molecular structure; Oxygen; Physical chemistry; Solid state physics; Charge transfer mechanism; Electronic structure; Oxygen bonding; Polyacetylene chains; Polyacetylenes